Decision making in the product portfolio: Methods adopted by Brazil's innovative companies (2015)
Product portfolio management is one of the leading contemporary trends in innovation strategy and R and D management. This paper aims to present and analyze methods that companies from the electronics and computer sectors adopt for decision making in their portfolios. A survey that collected information from 71 companies operating in Brazil was carried out, and it was noted that despite the financial methods, market research, and mapping being employed by some firms to base decision making on their product portfolios, most of them rely upon the informal decisions of senior management. In this way, the results of this survey indicate that, in addition to the formal methods, aspects of the influence and bargaining power of leaders must also be considered when analyzing and proposing management practices related to product portfolios.